Antioxidant Peptides from Proteins: Separation, Identification, Mechanisms, and Applications in Food Systems - Khatun, Most. Sharmin (Peneliti Teknologi Teknik Indonesia, 2025)
With an emphasis on their identification, separation, modes of action, and possible uses in food systems, this work offers a thorough investigation of antioxidant peptides generated from bioactive proteins. Antioxidant peptides are essential for combatting free radicals and averting oxidative damage. They are often generated by the enzymatic degradation of proteins from diverse sources, including plants, animal, and marine sources. High-performance liquid chromatography (HPLC), ultrafiltration, membrane filtration, and mass spectrometry are some of the sophisticated techniques used in the separation and identification of these peptides. These techniques enable accurate isolation and characterization. It's important to comprehend the processes by which these peptides exercise their antioxidant benefits; research suggests that their main modes of action include suppression of lipid peroxidation, metal ion chelation, and free radical scavenging. These bioactive peptides have a great deal of promise to improve food items' functional and nutritional qualities. Their integration into food systems can enhance their nutritional content, self-life, and health advantages, making them important components in the creation of functional meals. While the study highlights the promising potential of bioactive peptides, further research is essential to evaluate their stability, bioavailability, and safety under real-world conditions. Factors such as gastrointestinal degradation, absorption efficiency, and potential toxicity must be thoroughly assessed to ensure practical applicability. In addition, this work addresses the difficulties pertaining to these peptides' stability and bioavailability in food matrices and identifies areas for future investigation to maximize their application in the food sector.